Influence of Supply Chain Management on Production Cost and Productivity-A Case Study - Nigam, Akash; Singh, Vineet; Kumar, Niraj; Maheswari, Anurag (International Journal of Engineering and Technology, 2018)
Besides several other factors, in this study found that, production cost and productivity depends upon the supply chain management, because, it boosts some special objectives in the Plant/Company/Organization etc. The main objective governed by supply chain management is â€œThe right quality, in quick way, at right time, in flexible and cheap way available at correct place. On the basis of this study, we conclude that production cost is found to decrease after supply chain management. On the other way the productivity is found to increase with supply chain managementâ€.Â Â